1970
DOI: 10.24843/mip.2013.v16.i01.p02
|View full text |Cite
|
Sign up to set email alerts
|

Kebutuhan Energi Dan Protein Untuk Hidup Pokok Dan Pertumbuhan Pada Ayam Kampung Umur 10-20 Minggu

Abstract: Penelitian ditujukan untuk menghitung kebutuhan energi dan protein untuk hidup pokok dan untuk pertumbuhan pada ayam kampung umur 10-20 minggu. Sembilan puluh enam ekor ayam kampung umur 10 minggu yang dibagi dalam 4 kelompok perlakuan yaitu ayam yang diberikan ransum mengandung 3100 k.kal ME/kg dan 22% protein (perlakuan A), ransum yang mengandung 3000 K.kal ME/kg dan 20% protein (perlakuan B), ransum yang mengandung 2900 K.kal ME/kg dan 18% protein (perlakuan C) dan ransum yang mengandung 2800 K.kal ME/kg da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
7
1
1
Order By: Relevance
“…The additional body weight of native chickens fed a protein level ration of 16%, 18% and 20%, respectively, 4.9%, 14.6% and 15.5% was significantly higher (P<0.05) compared to the protein level of 14%. Similar results were presented by Mahardika et al (2013), Ariesta et al (2015) that the best performance of free-range chicken is at a protein level of 18% with an energy of 2900kcal/kg or 3000 kcal/kg. There is a close correlation (relationship) between protein level and weight gain of native chickens (Figure 2) with R2=0.9338 with Y = 531.56 ln X -291.28.…”
Section: Performance Of Kampung Chickens During the Growing Period (2...supporting
confidence: 83%
See 1 more Smart Citation
“…The additional body weight of native chickens fed a protein level ration of 16%, 18% and 20%, respectively, 4.9%, 14.6% and 15.5% was significantly higher (P<0.05) compared to the protein level of 14%. Similar results were presented by Mahardika et al (2013), Ariesta et al (2015) that the best performance of free-range chicken is at a protein level of 18% with an energy of 2900kcal/kg or 3000 kcal/kg. There is a close correlation (relationship) between protein level and weight gain of native chickens (Figure 2) with R2=0.9338 with Y = 531.56 ln X -291.28.…”
Section: Performance Of Kampung Chickens During the Growing Period (2...supporting
confidence: 83%
“…It was found that the decrease in ration protein had no maximal effect on the growth of KUB chickens aged 7-12 weeks and had an impact on the low efficiency of the use of rations with the FCR values obtained ranging from 3.7 to 4.4. Mahardika et al (2013), gave free-range chicken rations containing 3100 k.cal ME/kg and 22% protein, rations containing 3000 K.cal ME/kg and 20% protein, rations containing 2900 K.cal ME/kg and 18% protein and ration containing 2800 K.cal ME/kg and 16% protein. Free-range chicken rations aged 10-20 weeks with energy content at the level of 2,900 kcal/kg and 18% protein rations further increased the ration conversion value between 7.…”
mentioning
confidence: 98%
“…The protein consumed will be synthesized into amino acids and used for the growth and formation of meat [7]. Low protein in the feed will lead to decreased growth, as less protein is used to structure the components of the poultry body [12]. The use of Kurtus gulliver fish meal is as much as 15% able to meet the protein needs of poultry livestock.…”
Section: Potential Of Nursery Fish Meal (Kurtus Gulliver)mentioning
confidence: 99%
“…Hasil analisis Duncan menunjukkan bahwa perlakuan berbeda nyata (P<0,05) terhadap konsumsi ransum umur 14 -16 minggu, dimana perlakuan R0 berbeda nyata dengan perlakuan R1, R2 dan R3 sedangkan R1 tidak berbeda nyata (P>0,05) dengan perlakuan R2 dan R3. Hasil penelitian ini pada minggu ke 10-12 memiliki nilai yang lebih tinggi dari yang ditemukan oleh (Hery Irawan et al 2018) yaitu konsumsi ransummnya 57,79 -59,77 g/ekor/hari, dan juga lebih tinngi dari yang ditemukan oleh (Mahardika 2013) yaitu konsumsi ransumnya 50,34-61,43 g/ekor/hari.…”
Section: Pengaruh Perlakuan Terhadap Konsumsi Ransumunclassified